2021
DOI: 10.3390/cancers13235953
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor Membrane Component (PGRMC)1 and PGRMC2 and Their Roles in Ovarian and Endometrial Cancer

Abstract: Cancers of the female reproductive tract are both lethal and highly prevalent. For example, the five-year survival rate of women diagnosed with ovarian cancer is still less than 50%, and endometrial cancer is the fourth most common cancer in women with > 65,000 new cases in the United States in 2020. Among the many genes already established as key participants in ovarian and endometrial oncogenesis, progesterone receptor membrane component (PGRMC)1 and PGRMC2 have gained recent attention given that there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 107 publications
1
15
0
1
Order By: Relevance
“…Peluso and Pru [181] report that PGRMC1 associates with eukaryotic ribosomal translation initiation factors. In a pilot co-IP and proteomic protein identification experiment, Sarah Teakel in the author's lab had also identified ribosomal proteins in the co-IP pellets using HA-tagged PGRMC1 as bait.…”
Section: Ribosomal Interactions and Translational Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Peluso and Pru [181] report that PGRMC1 associates with eukaryotic ribosomal translation initiation factors. In a pilot co-IP and proteomic protein identification experiment, Sarah Teakel in the author's lab had also identified ribosomal proteins in the co-IP pellets using HA-tagged PGRMC1 as bait.…”
Section: Ribosomal Interactions and Translational Controlmentioning
confidence: 99%
“…We also already had the proteomics pathways analysis that was later published in 2020 [50], suggesting that PGRMC1 phosphorylation status could affect the abundance of some proteins involved in translation, but also that the dramatic changes in protein abundance profiles that we observed could be due to alterations in the subset of cellular mRNAs being translated. That prompted the author to investigate hints of ribosomal association from published resources, where The Human Protein Atlas reported prominent localization of PGRMC1 to the nucleolus, the site of ribosome biogenesis, and speculate that PGRMC1 "may affect the composition of ribosomes, translation initiation factors" [47], as cited by Peluso and Pru [181]. Terzaghi et al [182] later reported the nucleolar localization (i.e., the site of ribosomal RNA synthesis and pre-ribosomal particle assembly [183]) of PGRMC1 in bovine granulosa cells and oocytes.…”
Section: Ribosomal Interactions and Translational Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the PR is primarily known for its function as a ligand-activated transcription factor, its interaction with P4 also triggers rapid or transcription-independent effects. Immediate effects mainly occur through the activation of mPRs [ 6 ] and PGRMCs [ 7 , 8 , 9 ], whereas nuclear actions are exerted by the PR [ 10 ], but the latter is the only one that can exert both effects. In addition to the domains involved in its function as a transcription factor, the PR possesses a polyproline-rich (PXPP) motif between aa 421 and 428 that binds to the SH3 domains of several cytoplasmic molecules, including cSrc ( Figure 1 ), hematopoietic cell kinase (HCK), Fyn, and other kinases or adapter proteins such as the regulatory subunit of PI3K (p85), CRK proto-oncogene adaptor protein (Crk), and growth factor receptor-bound protein 2 (Grb2) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary goal of this review article is to highlight the current knowledge of PGRMC1 function in regulating mammalian cell proliferation, specifically by mechanisms set in motion during the progression of cell division (M phase/cytokinesis), which, so far, has received less attention from the scientific community. Although PGRMC1, together with its partner PGRMC2, participates in many other functions that impact cell proliferation, such as cell viability and apoptosis and entry into the cell cycle, these functions have been reviewed elsewhere and will not be further discussed here [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%